Exciton-polariton ring Josephson junction - Nina Voronova; Anna Grudinina; Riccardo Panico; Dimitris Trypogeorgos; Milena De Giorgi; Kirk Baldwin; Loren Pfeiffer; Daniele Sanvitto; Dario Ballarini (Nature Communications)
Abstract Macroscopic coherence in quantum fluids allows the observation of interference effects in their wavefunctions, and enables applications such as superconducting quantum interference devices based on Josephson tunneling. The Josephson effect manifests in both fermionic and bosonic systems, and has been well studied in superfluid helium and atomic Bose-Einstein condensates. In exciton-polariton condensates—that offer a path to integrated semiconductor platforms—creating weak links in ring geometries has so far remained challenging. In this work, we realize a Josephson junction in a polariton ring condensate. Using optical control of the barrier, we induce net circulation around the ring and demonstrate both superfluid-hydrodynamic and the Josephson regime characterized by a sinusoidal tunneling current. Our theory in terms of the free-energy landscapes explains the appearance of these regimes using experimental values. These results show that weak links in ring condensates can be explored in optical integrated circuits and hold potential for room-temperature applications.